Solid Ivory - Cameron, Peter 1959- (Corsair, 2021)
"The irreverent, brilliant memoirs of the legendary filmmaker James Ivory. In Solid Ivory, Academy Award-winning filmmaker James Ivory, a partner in the legendary Merchant Ivory Productions and director of A Room with a View, Howards End, Maurice, and The Remains of the Day, tells stories from the remarkable life and career of one of the most influential directors of his time into a carefully crafted mosaic of memories, portraits, and reflections. At times, they touch on his love affairs as he looks back coolly, and with unexpected frankness. From first meeting his long-time collaborator and life partner Ismail Merchant at the Indian Consulate in New York to winning an Academy Award at eighty-nine for Call Me By Your Name; from seeing his first film at five in Klamath Falls, Oregon to memories of Satyajit Ray, Federico Fellini, Vanessa Redgrave, George Cukor, Kenneth Clark, Bruce Chatwin, Ruth Prawer Jhabvala, and Ismail Merchant-Ivory writes with invariable fluency, wit and perception about what made him who he is and how he made the movies for which he is known and loved. Solid Ivory is an utterly winning portrait of an extraordinary life told by an unmatched storyteller"--Publisher's description
Keywords: Directors; Ivory, James; Motion picture producers and directors / United States / Biography; Gay motion picture producers and directors / United States / Biography; Gay motion picture producers and directors; Motion picture producers and directors; United States; Självbiografier; Regissörer; Biographies